2014
DOI: 10.5709/ce.1897-9254.137
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border commuting and migration intentions: the roles of risk aversion and time preference

Abstract: 137This article analyses the effects of individual risk aversion and time preference on cross-border mobility intentions using a theoretical and empirical model. The paper extends the previous literature by considering both cross-border commuting and migration as modes of mobility. The theoretical model shows that risk aversion has a negative effect on the willingness to migrate and to commute while the effect of time preference depends on expectations about the development of future wages in the home country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Previous studies show that risk averse individuals are less likely to migrate (Jaeger et al, ) and, when they do migrate, to move to locations culturally similar to home (Bauernschuster et al, ). Likewise, we control for students' time preference since migration is modelled in the neoclassical framework as an investment decision that involves benefits to be collected in the future in return to initial costs (Gibson & McKenzie, ; Nowotny, ). Hence, individuals who are more patient are expected to be more likely to migrate than individuals who are impatient.…”
Section: Datamentioning
confidence: 99%
“…Previous studies show that risk averse individuals are less likely to migrate (Jaeger et al, ) and, when they do migrate, to move to locations culturally similar to home (Bauernschuster et al, ). Likewise, we control for students' time preference since migration is modelled in the neoclassical framework as an investment decision that involves benefits to be collected in the future in return to initial costs (Gibson & McKenzie, ; Nowotny, ). Hence, individuals who are more patient are expected to be more likely to migrate than individuals who are impatient.…”
Section: Datamentioning
confidence: 99%
“…This (11)(12)(13)(14)(15)(16)(17)(18)(19) The difference in findings may be explained by the difference in samples and/or differences in uncertainty related to the specific push and pull factors of the home and destination country. Risk averse GPs may be more likely to migrate due to the lower levels of uncertainty around clinical and career domains in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals vary widely in their attitude towards risk, and risk attitude correlates with a range of behaviours including clinical decision-making, such as triage decisions for emergency patients (10). In the economics literature it has been recognised that risk attitude plays a role in migration decisions: several empirical studies have confirmed that risk seeking individuals are more likely to migrate (11)(12)(13)(14)(15)(16)(17)(18)(19). However, none of the previous studies have focused on health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Because extraverts are more adventurous and optimistic, this could result in the fact that they perceive the psychic costs of 22 On the relation between risk preference and migration decisions, see Massey (1990) and Jaeger et al (2010). For the relation between time preference and migration decisions, see Bowles (1970) and Nowotny (2014). 23 As personality shapes preferences, preferences may also shape personality.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Previous studies showed that risk averse individuals are less likely to migrate (Jaeger et al, 2010) and, when they do migrate, to move to locations culturally similar to home (Bauernschuster et al, 2014). Likewise, we control for students' time preference 46 chapter since migration is modelled in the neoclassical framework as an investment decision that involves benefits to be collected in the future in return to initial costs (Gibson and McKenzie, 2011;Nowotny, 2014). Hence, individuals who are more patient are expected to be more likely to migrate than individuals who are impatient.…”
Section: Control Variablesmentioning
confidence: 99%